Quality of life improvement in concurrent septorhinoplasty and endoscopic sinus surgery - Bulut, Cem; Lippert, Burkard M.; Riedel, Frank; Plath, Michaela; Hohenberger, Ralph (The laryngoscope, 2024)
Objectives Septorhinoplasty (SRPL) and functional endoscopic sinus surgery (FESS) are two frequently performed surgeries to improve quality of life (QoL) in patients with nasal symptoms. It has been demonstrated as a safe combination regarding complication rates, but patient satisfaction in concurrent surgery has not been adequately studied yet. Methods Patients undergoing sole FESS due to chronic rhinosinusitis (n = 57), sole SRPL (n = 148), and concurrent surgery (n = 62) were prospectively evaluated for their disease-specific QoL before and one year after surgery. Each procedure was performed by the same surgeon (OCB). For SRPL, the patient-reported outcome measures Rhinoplasty Outcomes Evaluation (ROE) and Functional Rhinoplasty Outcome Inventory (FROI-17) were utilized, and for chronic rhinosinusitis, the Sino-Nasal Outcome Test-22 (SNOT22). Results All three groups showed significant improvement in the postoperative QoL measurements (all p < 0.01). The postoperative improvements were slightly smaller in the concurrent surgery group compared with the single surgery groups measured with ROE (combined: +55.2 ± 9.3, single: +58.8 ± 9.8, p = 0.02), FROI total score (combined: +47.6 ± 5.2, single: +49 ± 5.4; p = 0.08) and SNOT22 (combined: +33.1 ± 6.7, single +34.5 ± 7, p = 0.26). Conclusions SRPL, FESS, and combined surgery improve disease-specific QoL. When applicable, surgeons may offer the benefits of a combined procedure without compromising the QoL gain. Level of Evidence Level 3 Laryngoscope, 2023